MENGEMBANGKAN SISTEM KOMPENSASI BERBASIS KINERJA DI RUMAH SAKIT HARAPAN MAGELANG - Tri Juli Wati; Sugianto Adisaputro; Andreasta Meliala (Journal of Health Service Management, 2016)
Background: Harapan Hospital has started performance appraisal toward employees since 2010. The result of these performance appraisal become the base for the following year's payment. Within five years of performance appraisal, the result hasn't improved, but decreased instead. On the other side, employee's salary continuously increased. So, we can say that the compensation which is received by the employee isn't relevant with their performance appraisal, and doesn't affect the performance's improvement, therefore evaluations and improvements on the recent compensation system are necessary. Objective: The goal of this research was to develop a performance-based compensation system in Harapan Hospital Magelang. Methods: This research is a case study research with a case study research design type 1, which means holistic single case design. Results: Four factors that based the completeness of the Pay Model as the foundation of the payment structure, is yet to be fulfifilled by the recent payment system. Performance appraisal that have been used so far is incapable of pushing better performance, because the guide used during the performance appraisal are too subjective that it can't diffffer each employee's capabilities. Performance appraisal results today become the base of the employee's salary, and this caused uncertainty about the salary changes. Incentive is being given equally. The perception of compensation system and its component are still yet to be well understood by neither the company nor the employee. There is still yet to be any agreement in formulating performance-based compensation system because of the employee's pessimistic behaviour and their thought, which considers performance appraisal nothing more than routines for formality. Conclusion: The completeness of Pay Model is yet to be based on performance based compensation system which are still valid, so more evaluations and improvements have to be done, which would resulted with a reliable compensation structure that can be formulated and able to become an attraction for potential employees as well as becoming a pushing factor for performance's improvement.